Full mouth rehabilitation of severely worn out deciduous dentition in conjunction with crown lengthening procedure: A case report - KP., Divakar; Nair, Anoop; Regish, KM.; Sharma, Ashu (International Journal of Dental Research, 2014)
In order to restore severely attrited deciduous teeth, surgical intervention in the form of a crown-lengthening procedure may be required. And also, proper diagnosis and treatment sequencing is critical to obtain a successful results. Adequate diagnostic wax-up ensures good esthetics and healthy periodontal tissue. This clinical case report describes a diagnostically based protocol for restoration on deciduous dentition with crown lengthening procedure and full mouth rehabilitation with porcelain fused to metal, metal and composite crowns.   Keywords: Deciduous Dentition, Diagnostic Wax Up, Full Mouth Rehabilitation, Surgical Crown Lengthening.